Cementless fixation in Oxford Unicompartmental Knee Replacement: A multicentre study of 1000 knees - Liddle, A; Pit, H; O'Brien, S; Doran, E; Penny, I; Hooper, G; Burn, P; Dodd, C; Beverl, D; Maxwell, A; Murray, D; Pit, H; et al. (British Editorial Society of Bone and Joint Surgery, 2013)
The Cementless Oxford Unicompartmental Knee Replacement (OUKR) was developed to address problems related to cementation, and has been demonstrated in a randomised study to have similar clinical outcomes with fewer radiolucencies than observed with the cemented device. However, before its widespread use it is necessary to clarify contraindications and assess the complications. This requires a larger study than any previously published. We present a prospective multicentre series of 1000 cementless OUKRs in 881 patients at a minimum follow-up of one year. All patients had radiological assessment aligned to the bone-implant interfaces and clinical scores. Analysis was performed at a mean of 38.2 months (19 to 88) following surgery. A total of 17 patients died (comprising 19 knees (1.9%)), none as a result of surgery; there were no tibial or femoral loosenings. A total of 19 knees (1.9%) had significant implant-related complications or required revision. Implant survival at six years was 97.2%, and there was a partial radiolucency at the bone-implant interface in 72 knees (8.9%), with no complete radiolucencies. There was no significant increase in complication rate compared with cemented fixation (p = 0.87), and no specific contraindications to cementless fixation were identified. Cementless OUKR appears to be safe and reproducible in patients with end-stage anteromedial osteoarthritis of the knee, with radiological evidence of improved fixation compared with previous reports using cemented fixation.